Web-Based E-Location of A Palm Oil Processing Factory in Dharmasraya Regency - ANISYA, ANISYA; Warman, Indra; Minarni, Minarni; Wira Trise Putra, Dede; Irawan, Boby; Yoga Swara, Ganda; Mandarani, Putri (KH. A. Wahab Hasbullah University, 2025)
Given the significance of oil palm plantations in contributing to the economy of Dharmasraya Regency, especially for industry players seeking suitable palm oil processing facilities, there is a need for detailed and easily accessible information. One approach to providing quick and convenient access to the locations of palm oil processing plants is through E-Location technology. E-Location is an electronic information system that displays a distribution map of palm oil processing plants in Dharmasraya Regency. This study aims to create a web-based E-Location information system using the CodeIgniter framework and Open Street Map (OSM) mapping software, facilitating easy access to information on the locations of Palm Oil Processing (POP) in Dharmasraya Regency. This system will enable users to view the distribution of POP locations and access a range of related information. The research results on the Design of a Web-Based Palm Oil Processing Plant E-Location Information System in Dharmasraya Regency show that this system is effective for viewing the distribution map and detailed information about palm oil processing plants in the region. Available information includes company profiles, maximum processing capacity for Fresh Fruit Bunches (FFB), number of employees, incoming palm oil volume, oil yield, kernel yield, and average annual oil yield.